Lignin in Place of Carbon Black for Ethylene-Propylene-Diene-Monomer Based Automotive Sealing Profiles - Bayram Poyraz; Yusuf Güner; Ayhan Tozluoglu; Rıdvan Yamanoğlu; Zeki Candan; Murat Şen (BioResources)
This study examined the effects of lignin used in EPDM elastomer composites in place of carbon black. For that purpose, lignin was added in amounts of 3.5, 7, and 10.5 phr to investigate the chemical, thermal, rheological, mechanical, and morphological properties of the EPDM elastomers. At the end of the study, tear strength and elongation were enhanced, whereas thermal stability was lowered due to the lignin. The lignin facilitated the vulcanization process and improved the torque values. In the morphology, the lignin was dispersed homogeneously in the matrix, and no voids or cracks were observed except with 10.5 phr. In conclusion, when incorporated at a specified ratio, lignin is economical and provides ecological benefits. Its use as a natural filler can be recommended to automotive industries to provide enhanced properties and ecological properties as a substitute for carbon black.